PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN MUSI RAWAS UTARA - Rinaldo Rinaldo; Effendi Effendi; Yulpa Raberta (Jurnal Interprof, 2025)
The problem in this research is that bosses too authoritarian so that staff feel uncomfortable, lack of work so that many jobs are neglected and lack of encouragement to have timely initiatives in completing reports. The results of the research testing the first hypothesis, namely that the leadership style variable has a significant influence on employee performance (Y) at a significant level of 0.05 because t count (17.999) > t table (1.666). Organizational culture variable has a significant influence on performance, because count (10,755) > t table (1.666). Work discipline variable has a significant effect on performance because t count (14,289) > t table (1.666). The results of the calculation of the value of f, obtained the value of f count 138.137 > f table 3.12 so that there is a simultaneous influence between leadership styles, Organizational culture, and work discipline on employee performance and obtained f count 138.137 > f table 3.12.